Usefulness of right ventricular strain assessment in submassive pulmonary thromboembolism undergoing ultrasound‐facilitated thrombolysis. Issue 8 (8th August 2019) - Dod, Harvinder S.; Nanda, Amit; Nanda, Navin C.; Klas, Berthold; Singh, Satinder; Salama, Ahmed Y.; Akdogan, Raziye E.; Fadala, Hanan; Abdelsalam, Mahmoud G. A.; Ahmed, Mohamed; Bedi, Rohil; Dod, Sachin; et al.
Abstract: Massive and submassive pulmonary thromboembolism carry significant morbidity and mortality. We present an elderly female who was diagnosed with a submassive pulmonary embolism by computed tomographic angiography and treated with ultrasound‐facilitated thrombolysis (UFT). This case demonstrates the usefulness of right ventricular longitudinal strain measurements by two‐dimensional speckle tracking echocardiography in the evaluation of right ventricular function before and after UFT. Evaluation of right ventricle longitudinal strain by speckle tracking echocardiography may supplement other parameters in the assessment of right ventricular function in these patients.